Rechstvacuum: Making of Authentic Deed for Persons with the Blind Persons - Muhammad Alvin Nugraha; Muchammad Ali Safa’at; Yenny Eta Widyanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Legal certainty is an integral part of the anatomy of the purpose of the law being formed. One of the premises that was built in assembling this anatomy occurred when we discussed the amendment of the deed carried out by persons with disabilities (people with visual impairments). Where, in principle, a notary as a public official is obliged to make sure that the deed made is understood by the appearers. When linking the aspects of Persons with Disabilities in Article 43 of the UUJN there is a provision that the Article provides legal guarantees for notarial products using an understandable language. This scheme then leads to the question that if the Notary Product uses Article 43 paragraph (1) of the UUJN, the deed must be made in Indonesian, is it written using the alphabet or using Braille?